Pengaruh Penambahan Template Polietilen Glikol Terhadap Karakter -Al2O3 dari Kaolin - Sunardi Sunardi; Lilik Nofianti; Utami Irawati (Jurnal Fisika FLUX, 2020)
Synthesis of g-Al2O3 from Tatakan, South Kalimantan kaolin using simple methods: metakaolinization, dealumination, precipitation process using polyethylene glycol (PEG-6000) as a structure directing agent, calcination steps, and characterization of its products have been presented. The purified kaolin was metakaolinized and dealuminated to get amorphous aluminum hydroxide.  After that, the sample was precipitated using the various concentration of PEG and NH4OH as the precipitating agent. Calcination process was carried out at calcined at a temperature of 700°C for 3 hours. Based on the FTIR spectra and X-ray diffraction of the g-Al2O3 obtained was similar to that of commercial g-Al2O3. The highest crystallinity of g-Al2O3 was formed when using twice of critical micelle concentration of PEG (10-3 mol/L).  This simple process is an industrially practicable substitute to the Bayer process